Kompetensi, Motivasi, Kompensasi Terhadap Kinerja Pustakawan Di UPT Perpustakaan Proklamator Bung Karno - Hanafi, Hanafi; Mulyaningtiyas, Ratna Dewi (Otonomi, 2025)
This study aims to determine the Influence of Competence, Motivation and Compensation on the Performance of Librarians in UPT. Perpustakaan Proklamator Bung Karno. Librarian performance is the implementation of the functions required of a librarian, both deeds, achievements, and skills in completing work. Competence is the main requirement in performance, because with competence, librarians will complete their assigned work well. While motivation is a reason or drive for someone to do something. Compensation will have a positive impact on the institution. For employees, compensation can meet the needs of life. In this study, the author uses a quantitative approach. The sample took the entire population, which amounted to 56 librarians. In this study, indicators and variables of indicators and competency variables showed 3.92, for motivation showed 3.97. compensation shows 3.95 and Performance shows 3.88. The average value of the variables of competence, motivation, compensation and performance is in the medium category. To find out the relationship between variables, simple regression analysis and multiple linear regression were used. The results of the study showed that there was an influence both individually and together on the variables of Competence, motivation and compensation on the performance of UPT. Perpustakaan Proklamator Bung Karno librarians.